أسباب الإعراض عن الخطاب الدعوي في القرآن الكريم سورتي الأعراف والقصص نموذجا - زلومة رقية (University of Eloued جامعة الوادي, 2023)
"لم تنفك آيات القرآن الكريم وأحاديث الرسول صلى الله عليه وسلم من التأكيد على ضرورة احتكام الخطاب الدعوي إلى جملة من القواعد والأصول وانضباطه بمجموعة من الضوابط والشروط التي تعين على نجاح الدعوة إلى الله وتأثيرها، وتساعد في فاعليتها وقوتها، وتسهم في صيرورتها إلى أهدافها وغاياتها المرجوة منها. وإن الدارس لكتاب الله الكريم وسنة الرسول صلى الله عليه وسلم ليجد التوجيه المستمر للدعاة إلى الله في كل عصر وزمان إلى ما ينبغي أن يتحقق في خطابهم للناس من أوصاف تمكِّن من النفاذ إلى عقول المدعوين وقلوبهم، ومن النجاح في صياغة أفكارهم وشخصياتهم، ومن التأثير في إصلاح حياتهم، ومن القدرة على تحويل مسار الأفراد والمجتمعات من طريق الانحراف والفساد، إلى طريق النجاة الاستقامة والصلاح، وتهدف هذه الدراسة إلى بيان واقع الخطاب الدعوي وأهميته وأهدافه وضوابطه وأساليبه وكذا معنى الإعراض عن الخطاب الدعوي وأسبابه سواء من خلال الواقع المعاش في هذا العصر أو من خلال القران الكريم وقصص الأنبياء مع أقوامهم واستنباط ما يقال من حوارات وتفاصيل مع تخصيص سورتي الأعراف والقصص بشكل مفصل أكثر لما تحويه من آيات"The verses of the Holy Quran and the sayings of the Prophet (peace be upon him) have consistently emphasized the necessity of adhering to a set of rules، principles، and guidelines in delivering religious discourse. These rules and conditions are essential for the success and impact of the call to Allah، enhancing its effectiveness and strength، and helping it achieve its desired goals and objectives. A careful study of the Quran and the Sunnah reveals continuous guidance for the callers to Allah in every era and time. They are guided in crafting their discourse to possess qualities that enable them to reach the minds and hearts of those they invite، shape their thoughts and personalities، influence the reform of their lives، and redirect individuals and communities from the path of deviation and corruption to the path of salvation، uprightness، and righteousness. This study aims to elucidate the reality، importance، objectives، regulations، and methods of religious discourse، as well as the concept of turning away from it. It examines the reasons for this turning away، whether through the lens of contemporary circumstances or through the stories of the Prophets and their peoples. It extracts insights from dialogues and details، with a particular focus on Surah Al-A'raf and Surah Al-Qasas due to their rich content of verses and stories that manifest the nature of religious discourse clearly. Through this examination، it becomes possible to identify the causes and forms of turning away from religious discourse." وقصص يتجلى فيها الخطاب الدعوي بشكل واضح ومن خلال التفسير يمكن تحديد أسباب وأشكال الإعراض عن الخطاب الدعوي."
مدكرة ماستر دعوة واعلام
Keywords: الاعراض; الخطاب الدعوي; القرآن الكريم; the Holy Quran; advocacy speech; causes